2011
DOI: 10.1074/jbc.m111.236877
|View full text |Cite
|
Sign up to set email alerts
|

Side Chain-oxidized Oxysterols Regulate the Brain Renin-Angiotensin System through a Liver X Receptor-dependent Mechanism

Abstract: Disturbances in cholesterol metabolism have been associated with hypertension and neurodegenerative disorders. Because cholesterol metabolism in the brain is efficiently separated from plasma cholesterol by the blood-brain barrier (BBB), it is an unsolved paradox how high blood cholesterol can cause an effect in the brain. Here, we discuss the possibility that cholesterol metabolites permeable to the BBB might account for these effects. We show that 27-hydroxycholesterol (27-OH) and 24S-hydroxycholesterol (24S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 51 publications
(54 reference statements)
3
44
0
Order By: Relevance
“…The brain of patients who had died with AD contained markedly increased levels of 27OH [8]. Under in vitro [9][10][11] as well as under some in vivo conditions [11], 27OH seems to accelerate neurodegenerative processes.…”
Section: Introductionmentioning
confidence: 95%
“…The brain of patients who had died with AD contained markedly increased levels of 27OH [8]. Under in vitro [9][10][11] as well as under some in vivo conditions [11], 27OH seems to accelerate neurodegenerative processes.…”
Section: Introductionmentioning
confidence: 95%
“…Decreased levels of 27-OHC have been observed in several neurodegenerative disorders including AD, HD, and PD [15]. 27-OHC may link high peripheral cholesterol with many CNS diseases through its ability to upregulate the brain renin-angiotensin system in an LXR-dependent manner [16]. Additionally, Zhang et al recently showed that peripheral injection of 27-OHC into rats upregulates LXRα and ATP-binding cassette transporter ABCA1 in the brain, downregulates HMG Co-A Reductase and LDLR, and produces dose-dependent impairments of spatial memory performance in the Morris Water Maze (MWM) task [17].…”
Section: Cholesterol Homeostasis In the Cnsmentioning
confidence: 99%
“…Furthermore, in an extensive study, we demonstrated that both 24S-OH and 27-OH upregulate several members of the brain RAS including AGT, ACE and AT1 receptor (AT1R). This modulation of the brain RAS by oxysterols was through a liver X receptor-dependent mechanism [7] . In AD, increased 27-OH levels in plasma and CSF correlated with enhanced CSF-ACE activity [11] , although CSF-ACE levels were reported to be decreased [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Given that 24S-OH and 27-OH were described as important modulators of AGT, renin, ACE and AT1R [7] , the purpose of the present study was to investigate the effects of these oxysterols on ACE2 and MasR, in order to gain insight into how they affect this brain RAS axis. As shown in figure 1 b, significant increases in both ACE2 and MasR expressions were found in rat primary neurons treated with a physiological concentration (1 M ) of 27-OH or 24S-OH for 24 h.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation